The witch of Blackbird Pond - Speare, Elizabeth George (New York Dell, 1993)
In 1687, Kit Tyler moves from the Caribbean to Connecticut Colony. Her friendship for a strange, old woman leads to her trial for witchcraft
English stories
2
Keywords: English stories